Prevalensi periodontitis pada pasien diabetes mellitus (Studi observasional di poliklinik penyakit dalam RSUP Dr. Sardjito) - Rezmelia Sari; Dahlia Herawati; Rizky Nurcahyanti; Pramudita Kusuma Wardani (Faculty of Dentistry, Universitas Gadjah Mada, 2017)
Prevalence of periodontal diseases in patients with diabetes mellitus (An observational study at internal medicine polyclinic in Dr. Sardjito General Hospital). Diabetes Mellitus (DM) is a chronic disease with an increasing prevalence and causes complications. The most frequent complication found in the oral cavity of patients with diabetes mellitus is periodontal diseases is characterized by the loss of tissue attachment. There have been numerous studies on the association of DM with periodontal diseases but there has not been any data on the prevalence of periodontal diseases in diabetic group, especially in Yogyakarta and Central Java. Dr. Sardjito General Hospital is a referral hospital in DIY and Central Java, so this study is expected to provide a picture regarding the level of periodontal tissue health among people in Yogyakarta and Central Java. This research was an observational study, involving 36 patients with DM according to criteria of the subjects: suffering from type 2 diabetes, being cooperative and willing to sign an informed consent. The controlled variables: being 40 – 60 years of age, having good oral hygiene (OHI) according to Green and Vermillion, taking neither antibiotics nor anti-inammatory drugs in the last 3 months, not having a history of other systemic diseases. Oral hygiene exams were carried out, followed by examination using probe WHO to determine if there is CAL. The data were presented descriptively. The results showed that the prevalence of periodontal diseases in patients with DM at Internal Medicine Polyclinic in Dr. Sardjito General Hospital is 88.24% with a mean of CAL distance of 4.6 mm. The conclusion of this study is that the prevalence of periodontal diseases in patients with DM is high although the oral hygiene status is good. ABSTRAKDiabetes Mellitus (DM) adalah penyakit kronis menahun dengan prevalensi yang semakin meningkat dan menimbulkan komplikasi. Komplikasi yang paling sering terjadi di rongga mulut pasien DM adalah periodontitis yang ditandai dengan kehilangan perlekatan jaringan. Penelitian tentang hubungan DM dengan periodontitis banyak dilakukan namun belum ditemukan data mengenai prevalensi periodontitis pada kelompok DM khususnya di DIY dan Jawa Tengah. RSUP Dr. Sardjito merupakan rumah sakit rujukan DIY dan Jawa Tengah sehingga penelitian ini diharapkan dapat memberi gambaran mengenai tingkat kesehatan jaringan periodontal di masyarakat DIY dan Jawa Tengah. Jenis penelitian ini adalah observasional dengan melibatkan 36 orang pasien DM sesuai kriteria subjek yaitu menderita DM tipe II, kooperatif dan bersedia menandatangani informed consent. Variabel terkendali yaitu usia 40 – 60 tahun, kebersihan mulut (OHI) menurut Green and Vermillion dalam kriteria baik, tidak menggunakan antibiotik dan antiinamasi dalam 3 bulan terakhir dan tidak memiliki riwayat penyakit sistemik lain. Dilakukan pemeriksaan kebersihan mulut dilanjutkan dengan pemeriksaan menggunakan probe WHO untuk menentukan ada tidaknya CAL. Data disajikan secara deskriptif. Hasil penelitian menunjukkan bahwa prevalensi periodontitis pada pasien DM di Poli Klinik Penyakit Dalam RSUP Dr. Sardjito adalah 88,24% dengan rata-rata jarak CAL adalah 4,6 mm. Kesimpulan penelitian ini adalah prevalensi periodontitis pada pasien DM tinggi walaupun status kebersihan mulut tergolong dalam kriteria baik.